PRAKTIK JUAL BELI BUAH-BUAHAN BERLABEL HARGA PERSPEKTIF HUKUM ISLAM - Ika (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
The Pendawan Village Fruit Market, Sambas District is one of the fruit markets where many traders use price labels in selling fruit. However, it is not uncommon for errors to occur in the fruit-selling process, namely the price of the fruit on the label does not match the original price, so buyers feel disadvantaged. Therefore, it is important to know how the process of buying and selling fruit using price labels at the Pendawan Village Fruit Market, Sambas District. The formulation of the research problem is: 1) How is the use of price labels in the Perspective of Islamic Law at the Pendawan Village Fruit Market, Sambas District? 2) What is the view of Islamic Economic Law on the use of price labels at the Pendawan Village Fruit Market, Sambas District? This type of research is qualitative research and the approach used is a descriptive approach. This research was conducted on existing social events. The data collection technique used three techniques: Observation, interview, and documentation. The results of this study successfully revealed that the Price Label Perspective of Islamic Law at the Pendawan Village Fruit Market, Sambas District, including the existence of fruit traders at the Pendawan Village Fruit Market, Sambas District who sell fruit that does not match the price label with the actual price, resulting in losses for buyers. Of course, this is a problem in the buying and selling process and there must be rules or laws that regulate this problem. Meanwhile, the view of Islamic Law on the Use of Price Labels at the Pendawan Village Fruit Market, Sambas District, is that it is not allowed. This is because the use of price labels that do not match the actual price can harm others, considering that acts that harm others are prohibited in Islam, this is in accordance with what is explained in the Al-Qur'an, Surah Asy-Syu'ara verse 81 and the Al-Qur'an, Surah An-Nisa verse 29.